Excitation functions and thinck target yields for deuteron induced reactions on zirconium - Wasilevsky, C.; Dos Santos, F.; Herreros Usher, O.; Nasslff, S. J. (Elsevier B.V., 1978)
Fil: Wasilevsky, C. Comisión Nacional de Energía Atómica; Argentina